A study on customer purchase decision on transportation service of good / Muhammad Fairos Mohamad Shah - Mohamad Shah, Muhamad Fairos (2013)
The purpose of this study was to identify the factors that affect the involvement of transportation of good. The factors relate are price,product,place and promotion were studied in MF Hot Trans 1 Sdn Bhd Glugor,Pulau Pinang. The population of this study is 125 respondents. The aim of this study is to enhance MF Hot Trans Sdn. Bhd was incorporated with the sole objective of providing the verification and re-verification services for all weighing and all measuring instruments use for trade in Malaysia. The company started operation on the 1998.This project paper will focus on how this firm performance during 14 years ago. Start from 1998 until 2012. This project paper will calculate the ratio analysis of this firm that been extract from income statement and balance sheet. To concrete this ratio, the researcher also includes a common size analysis as the side evidence about this company financial performance. The purpose of this analysis, to compare how the company performance throughout from 1998 until 2012.Data are being collected by interview, journal. Thus further studied being done to show how the financial position about this firm. The result indicates that, the used of these method contribute to the reasons and evidence that based on the customer purchase decision.